2014
DOI: 10.1021/jp4091602
|View full text |Cite
|
Sign up to set email alerts
|

Local Structures of Methanol–Water Binary Solutions Studied by Soft X-ray Absorption Spectroscopy

Abstract: Liquid methanol shows one- and two-dimensional (1D/2D) hydrogen bond (HB) networks, and liquid water shows three-dimensional (3D) HB networks. We have clearly found three different local structures around the methyl group of methanol-water binary solutions (CH3OH)X(H2O)1-X at different concentrations in C K-edge soft X-ray absorption spectroscopy (XAS). With the help of molecular dynamics simulations, we have discussed the concentration dependence of the hydrophobic interaction at the methyl group in the C K-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
91
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 77 publications
11
91
0
Order By: Relevance
“…[27][28][29][30][31][32] This has been supported by X-ray emission and X-ray absorption studies. [33][34][35] Dielectric relaxation and nuclear magnetic resonance spectroscopies support the clustering explanation while also revealing reduced liquid mobility. [36][37][38][39][40][41] Using Raman spectroscopy, Ben-Amotz et al have concluded that the observed clustering in alcohol-water mixtures is a result of random, rather than hydrophobic, interactions.…”
Section: -17mentioning
confidence: 61%
See 1 more Smart Citation
“…[27][28][29][30][31][32] This has been supported by X-ray emission and X-ray absorption studies. [33][34][35] Dielectric relaxation and nuclear magnetic resonance spectroscopies support the clustering explanation while also revealing reduced liquid mobility. [36][37][38][39][40][41] Using Raman spectroscopy, Ben-Amotz et al have concluded that the observed clustering in alcohol-water mixtures is a result of random, rather than hydrophobic, interactions.…”
Section: -17mentioning
confidence: 61%
“…Note that this is not in agreement with previous finding by Nagasaka et al who observed the absorption onset of methanol and water at the same energy. 34 Significant changes are observed in the pre-edge region of the alcohol spectra (533-535 eV) upon the addition of water (Fig. 2).…”
Section: Resultsmentioning
confidence: 94%
“…According to this interpretation, the presence of the composition-dependent anomalies can be ascribed to the formation of a low entropy cage of water with strong hydrogen-bonds around the alcohol molecules, which in this case would increase the structural ordering of bulk water. These ideas seem to have been confirmed by a series of experimental X-ray diffraction studies, in most cases complemented by molecular simulations [27,28]. In these studies it was found that adding methanol to water, enhances the local three dimensional network of water in the vicinity of the methanol molecules, which explains the decrease in the entropy of mixing and the considerable increase in the heat capacity at low alcohol concentrations.…”
Section: Introductionmentioning
confidence: 74%
“…[21][22][23][24][25][26][27][28][29] The effects of the local order can also be studied systematically by adsorption to metal surfaces, where different coverages yield structures ranging from gas-like to icelike. 16,17 The spectral changes for variations in pH have also been investigated, [30][31][32] as well as that of supercritical water 33 and water contained in reverse micelles.…”
Section: Introductionmentioning
confidence: 99%